Pengaruh Variasi Komposisi Dekomposer EM4 Dan Molase pada Pembuatan Pupuk Organik Cair Dari Limbah Budidaya Lele - Nanda Mustikarini; Anisa Ikaromah; Aris Supriyadi; Tri Adi Nugraha; Nazula Azzam Ma'ruf (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Catfish cultivation is widely cultivated by the Indonesian people and generally uses intensive methods so as to produce high stocking densities. Fish farming activities will produce wastewater in which organic residues can accumulate from feeding fish, manure, particles of fish feed residue, bacteria, and algae. In addition, catfish cultivators utilize the remaining water from catfish cultivation as plant fertilizer without further processing. This will affect other organisms in the soil, so it is necessary to research and manufacture liquid fertilizer from water left over from catfish farming. Liquid organic fertilizer is a fertilizer derived from organic materials from plants and animals that have undergone decomposition and have a liquid form of product. Liquid organic fertilizer is made by comparing the composition of the remaining water from catfish farming, EM4, and molasses. This aims to determine the effect of bioactivators for liquid organic fertilizer with water as a base material from catfish cultivation. The composition made is 1 liter of pure wastewater (sample A); 1 liter of pure waste, 20 ml of EM4, and 20 ml of molasses (sample B); 1 liter of pure waste, 10 ml of EM4, and 30 ml of molasses (sample C); and 1 liter of pure waste, 30 ml of EM4, and 10 ml of molasses (sample D) which were then kept in the mixture for 15 days in a closed manner. From these 4 variations, the results of testing pH, temperature and also organic C content were obtained where the temperature and pH tests met the quality standards for liquid organic fertilizers, while the organic C values did not meet the quality standards for liquid organic fertilizers.